Hierarchically Superstructured Metal Sulfides: Facile Perturbation‐Assisted Nanofusion Synthesis and Visible Light Photocatalytic Characterizations. Issue 12 (29th November 2016) - Yue, Yanfeng; Li, Yunchao; Bridges, Craig A.; Rother, Gernot; Zhang, Jinshui; Chen, Jihua; Hensley, Dale K.; Kidder, Michelle K.; Richardson, Bruce C.; Parans Paranthaman, Mariappan; Dai, Sheng
Abstract: A novel and simple perturbation‐assisted nanofusion (PNF) synthetic strategy was developed for the synthesis of stable hierarchically superstructured metal sulfides with controlled morphology. This promising approach is based on a kinetically controlled precipitation to simultaneously condense and re‐dissolve polymorphic nanocrystallites, and provides the resultant samples with a unique mesoporous framework. The PNF approach is environmentally friendly, produces gram‐scale products in a matter of hours, and is complimentary to the traditional hard or soft templating methods for the construction of mesoporous metal sulfides. PNF‐derived hierarchical porous CdS exhibited a vastly improved photocatalytic performance over its commercial bulk counterparts under visible light irradiation, demonstrating the advantage of the porous morphology for photocatalysis resulting from the enlarged surface area and the easy accessibility of the mesopores. Abstract : Nanofusion : Hierarchically superstructured metal sulfides were prepared through a facile perturbation‐assisted nanofusion (PNF) synthetic method with gram‐scale products produced in a matter of hours. In comparison to their commercial bulk counterparts, the hierarchical porous CdS exhibited exceptional photocatalytic performance under visible light irradiation, because of the enlarged surface and enhanced pore accessibility.